Pengaruh Partisipasi Anggaran, Kejelasan Sasaran Anggaran, Pengendalian Akuntansi dan Sistem Pelaporan terhadap Akuntabilitas Kinerja Instansi Pemerintah Daerah dengan Komitmen Organisasi Sebagai Variabel Pemoderasi - Beny Arifin W. (Journal of Accounting and Investment, 2012)
This research is conducted to examine the effect of budget participation, budget goal clarity, accounting control and reporting system on performance accountability of government agencies with organizational commitment as a moderating variable. The sample in this study was taken with a purposive sample of non probability sampling that adjusted with certain criteria or considerations. The sample in this study are structural officials in Pekalongan Regency which amounted to 90 respondents. The results of this study show that the participation of the budget, the budget goal clarity, accounting controls and reporting systems have significant positive effect to the performance accountability of government agencies. However, budget participation, budget goal clarity, accounting controls and reporting systems do not affect the performance accountability of government agencies with organizational commitment as moderating variable.